Dicrostonyx nelsoni Merriam 1900 - Don E. Wilson; Russell A. Mittermeier; Thomas E. Lacher, Jr (Lynx Edicions, 2017)
36. Nelson's Collared Lemming Dicrostonyx nelsoni French: Lemming de Nelson / German: Nelson-Halsbandlemming / Spanish: Lemming de collar de Nelson Other common names: St. Lawrence Island Collared Lemming Taxonomy. Dicrostonyx nelsoni Merriam, 1900, “St. Michaels [Norton Sound], Alaska.” Dicrostonyx nelsoni is monotypic and is not recognized as a distinct species by some, but instead considered a subspecies of D. groenlandicus. Other taxonomists, based on chromosomal differences and breeding studies, suggest that there are up to three species of collared lemming in Alaska alone. Distribution. W Alaska, from Seward Peninsula S to Alaska Peninsula and Unimak I (previously considered D. peninsulae), and including population on St. Lawrence I (previously considered D. exsul). Descriptive notes. Head—body 126-135 mm,tail 9-13 mm; weight 45-72 g. Nelson's Collared Lemming is stocky, with relatively short limbs and tail. It is seasonally dimorphic, white in winter and grayish brown in summer. There is usually a reddish collar in summer. Habitat. Drier and rockier shrublands and tundra of western Alaska. Food and Feeding. Nelson's Collared Lemming eats leaves, flowers, buds, and roots of shrubs, herbs, and sedges. Willows (Salix, Salicaceae) are especially important as a winter food. Breeding. Nelson's Collared Lemmings might breed year-round, with gestation averaging c.20 days and litters likely of 1-8 young. Activity patterns. Nelson’s Collared Lemming is terrestrial and probably active throughout the year, feeding day and night. Movements, Home range and Social organization. No information. Status and Conservation. Classified as Least Concern on The IUCN Red List. Bibliography. Bradley, Ammerman et al. (2014), Cassola (2016h), Fedorov & Goropashnaya (1999, 2016), Jar rell & Fredga (1993), MacDonald & Cook (2009), Musser & Carleton (2005), Rausch (1977), Rausch & Rausch (1972), Stenseth & Ims (1993), Wilson & Ruff (1999). Published as part of Don E. Wilson, Russell A. Mittermeier & ...